A Critical Analysis of the Representation of Migrants in Spanish Cinema (2021–2024) - Vilaró Moncasí, Arnau; López Ortega, Anna; Escobar-Vicent, Alejandro; Lavín, José M. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
The representation of immigration in post-pandemic Spanish cinema shows that, despite the increase in narratives about migration, these continue to be anchored in stereotypes and paternalistic ideas that strip immigrants of their real identity. This research proposes a specific taxonomy to analyze a sample of fiction films (2021-2024) featuring migrant characters. By applying the taxonomy, it is verified that, although migrant diversity in Spanish cinema has grown, its centrality, complexity, and prominence continue to lack representation in line with the demographic composition of today's society, maintaining obsolete narratives that are unrepresentative of reality.